Uji Aktivitas Antioksidan Ekstrak Etanol Daun Pepaya (Carica papaya L.) dengan Metode DPPH - Anggun Pratiwi; Razoki Razoki; Muhammad Yunus; Daimah Wirdatus Sanaun Harahap (Pusat Riset dan Inovasi Nasional, 2025)
Oxidative stress is a condition resulting from an imbalance between free radicals and the body's antioxidant system, which can damage cells and trigger degenerative diseases such as diabetes, cancer, atherosclerosis and heart disease. Antioxidants play an important role in neutralizing free radicals to prevent cell damage. Papaya leaves (Carica papaya L.) are known to contain bioactive compounds that have potential as a source of natural antioxidants. This study aims to test the antioxidant activity of papaya leaf ethanol extract using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, with quercetin as a comparator. Extraction was done by maceration using 80% ethanol. Antioxidant activity was measured based on the decrease in absorbance of DPPH solution at a wavelength of 517 nm using UV-Vis spectrophotometer. The results showed that papaya leaf extract had strong antioxidant activity with IC₅₀ value of 21.35 ppm, while quercetin was 4.84 ppm. Thus, the ethanol extract of papaya leaves showed high potential as an effective natural antioxidant.